Oil price shocks and Vietnam's macroeconomic fundamentals: quantile-on-quantile approach - Thuy Tien Ho (Cogent Economics & Finance, 2022)
This study aims to explore the asymmetric relationships between global oil prices and the selected Vietnam macroeconomic indicators using both quantile-on-quantile regression and Granger causality in quantile frameworks. The macroeconomic factors under study, as expected, have a strong relationship with oil price changes. The results suggest that oil prices have a positive impact on the exchange rate, inflation, GDP, and stock market prices across major quantiles, while there is a significantly negative relationship between the unemployment rate and oil prices in the middle-upper quantile. The results of this article offer considerable policy implications for governments, investors, and policymakers.
Keywords: G12; I32; O55; 330; macroeconomic factors; oil prices; quantile regression; causality; Vietnam